2012
DOI: 10.1371/journal.pone.0039311
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HAART on Alternative Reading Frame Immune Responses over the Course of HIV-1 Infection

Abstract: Background Translational errors can result in bypassing of the main viral protein reading frames and the production of alternate reading frame (ARF) or cryptic peptides. Within HIV, there are many such ARFs in both sense and the antisense directions of transcription. These ARFs have the potential to generate immunogenic peptides called cryptic epitopes (CE). Both antiretroviral drug therapy and the immune system exert a mutational pressure on HIV-1. Immune pressure exerted by ARF CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 51 publications
3
21
0
1
Order By: Relevance
“…Relative to their length and the frequency whereby they are targeted, responses to these ASPs compare well with observed reactivities to epitopes encoded in forward cryptic HIV reading frames (4) and response rates to well-studied regulatory HIV proteins, such as Tat, Vif, and Rev (19). The response rates are also comparable to activities reported by Champiat et al, who identified responses to ASPs that partially overlapped with four of our ASP sequences (6). Together, the present study corroborates earlier reports of responses to epitopes in alternative HIV reading frames and suggests that HIV may express several additional, relatively conserved proteins that may be under evolutionary constraints and thus exert hitherto-unknown functions.…”
Section: Irus-specific Cd8supporting
confidence: 87%
See 2 more Smart Citations
“…Relative to their length and the frequency whereby they are targeted, responses to these ASPs compare well with observed reactivities to epitopes encoded in forward cryptic HIV reading frames (4) and response rates to well-studied regulatory HIV proteins, such as Tat, Vif, and Rev (19). The response rates are also comparable to activities reported by Champiat et al, who identified responses to ASPs that partially overlapped with four of our ASP sequences (6). Together, the present study corroborates earlier reports of responses to epitopes in alternative HIV reading frames and suggests that HIV may express several additional, relatively conserved proteins that may be under evolutionary constraints and thus exert hitherto-unknown functions.…”
Section: Irus-specific Cd8supporting
confidence: 87%
“…Accumulating evidence indicates that in addition to CTL responses targeting known structural and nonstructural HIV proteins, CTL responses to epitopes in alternative reading frames (ARFs) of HIV can contribute to in vivo immune selection pressure (4)(5)(6). Importantly, these CTL responses are not limited to ARFs in the sense direction, but may also target antisense-encoded ARFs (5,6).…”
Section: Irus-specific Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…Using a selected set of CE (9–11 mers) based on HLA-I associated HIV-1 polymorphisms; we and others have previously shown that CE are frequently targeted during HIV-1 infection 39,40 . A recent paper illustrated enhanced ARF encoded immune responses in HIV infected patients receiving antiretroviral therapy (ART) 44 . Similar to our prior work 39 most of the peptides used in this study were derived from reverse frames.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our prior work 39 most of the peptides used in this study were derived from reverse frames. The T-cell responses in this study were examined in a small subset of HIV-1 infected individuals expressing HLA A*02, B*07 and B*58 alleles 44 . However, no study to date has assessed the frequency, functionality and biological significance of CE in context of specific HLA class I alleles associated with differential disease outcome.…”
Section: Introductionmentioning
confidence: 99%